Parlare parlato - VOGHERA, Maria (Sellerio, 2005)
The artiche presents two sections. The first one shows the ongoing nativization process of Italian, comparing the distribution of the use of Italian language and different vernaculars in different age brackets. The second one discusses the consequences on the linguistic dynamics within the Italian society and as far as the representation of Italian linguistic repertoire.